Discretized representations in V1 predict suboptimal orientation discrimination - Julien Corbo; O. Batuhan Erkat; John McClure; Hussein Khdour; Pierre-Olivier Polack (Nature Communications)
Abstract Neuronal population activity in sensory cortices is the substrate for perceptual decisions. Yet, we still do not understand how neuronal information content in sensory cortices relates to behavioral reports. To reconcile neurometric and psychometric performance, we recorded the activity of V1 neurons in mice performing a Go/NoGo orientation discrimination task. We found that, around the discrimination threshold, V1 does not represent the orientation of the stimuli as canonically expected. Instead, it forms categorical representations characterized by a relocation of activity at task-relevant domains of the orientation representational space. The relative neuronal activity at those discrete domains accurately predicted the probabilities of the animals’ decisions. Our results thus suggest that the categorical integration of discretized feature representations from sensory cortices explains perceptual decisions.